A longitudinal index study of orthodontic stability and relapse - Olive Richard J.; Basford Kaye E. (Sciendo, 2003)
Background: Previous studies of stability and relapse after orthodontic treatment report short-term stability is generally followed by slow relapse to the original condition. What these studies do not report is whether this relapse is continuous or interspersed with periods of improvement or stability.